Age‐based efficacy and safety of nivolumab for recurrent or metastatic head and neck squamous cell carcinoma: A multicenter retrospective study. Issue 6 (23rd June 2020) - Kondo, Takahito; Okamoto, Isaku; Sato, Hiroki; Koyama, Nobuyuki; Fushimi, Chihiro; Okada, Takuro; Masubuchi, Tatsuo; Miura, Kouki; Matsuki, Takashi; Yamashita, Taku; Omura, Go; Takahashi, Hideaki; et al.
Abstract: Aim: This study retrospectively investigated the efficacy and safety of nivolumab for patients with recurrent or metastatic head and neck squamous cell carcinoma (R/M HNSCC) classified using age <65 years as the cutoff. Methods: Overall, 88 patients with R/M HNSCC treated with nivolumab were classified into the young group (<65 years; n = 39) and elderly group (≥65 years; n = 49). Efficacy was evaluated using overall survival (OS), progression‐free survival (PFS), overall response rate (ORR) and disease control rate (DCR). Safety was evaluated considering immune‐related adverse events (irAEs). Results: The median OS was 9.7 and 8.6 months in the young and elderly groups, respectively. The 1‐year OS rate was 42.0% and 29.4% in the young and elderly groups, respectively. The median PFS was 3.0 and 4.2 months in the young and elderly groups, respectively. The 1‐year PFS rate was 30.0% and 27.9% in the young and elderly groups, respectively. In the young group, the ORR was 10.3% and DCR was 33.3%. In the elderly group, the ORR was 18.4% and DCR was 53.1%. There were no significant differences in OS, PFS, ORR, and DCR ( P = 0.36, 0.53, 0.29 and 0.06, respectively). Interstitial lung disease (ILD) as an irAE occurred in the young group at a significantly higher rate (20.5% vs 4.1%; P = 0.02). Conclusions: There were no significant differences in OS, PFS, ORR, and DCR between the young and elderly groups. DCR tended to be better in the elderly group ( P = 0.06). ILD occurred at a significantly higher rate in the young group.